The Effectiveness Of Constructivist Pedagogy On Mathematical Anxiety On The Students Of High I.Q. (Journal of Namibian Studies : History Politics Culture, 2022)
The students of the seventh class of the U.P. board living in Lucknow city were the population and all the 47 students of the seventh class of ‘Upper Primary School Mukarimnagar’ were the sample of the presented research. Purposive sampling was used to select the sample and out of 47 students in the class, 40 students were selected through a lottery system and matched on the basis of I.Q. Out of the 20 students in the experimental group, 11 students of high I.Q. and out of the 20 students existed in the control group, 10 students of high I.Q. existed in the experiment. Through ‘Non-Equivalent Post-Test-Only Control Group design’ the researcher taught all 11 students of the experimental group of high I.Q. using self-made constructivist pedagogy-based instructional material (teaching modules) and all the 10 students of the control group of high I.Q. were taught from the pre-determined unit of the class seventh math’s textbook through traditional teaching method using chalk and talk procedure till one and half months in every working day in the school. After this in the post-test, the data was collected on the mathematical anxiety of the students using a self-developed and standardized ‘Mathematical Anxiety Scale’. The normality of the experimental group of high I.Q. was found 0.082 and the control group was found 0.838. The homogeneity between both groups was found 0.265.  The mean of the scores obtained on the scale of the experimental group students was 102.55  and the mean of the control group students was 131.20. The t-value between both groups was found 12.34 with at 0.01 level of significance. The research explored that the mathematical anxiety of the students of the experimental group of high I.Q. was found 52.33% and the control group was found 67.0%. The experimental group students of high I.Q. have ‘average mathematical anxiety’ and the students of the control group of high I.Q. have ‘high mathematical anxiety’.